How can global guidelines support sustainable hygiene systems? - Joanna Esteves Mills; Ann Thomas; Nadia Abdalla; Rola Al-Emam; Kahtan Al-Shabi; Mary Eyram Ashinyo (BMJ Global Health, 2023)
According to consulted future guideline end-users, sustainable implementation of such recommendations to improve hand hygiene requires government-led system-strengthening approaches that build sustainable and resilient national systems.
Keywords: Sustainable hygiene; Global health guidelines